Languages and Compilers for Parallel Computing 25th International Workshop, LCPC 2012, Tokyo, Japan, September 11-13, 2012, Revised Selected Papers - Kasahara, Hironori; Kimura, Keiji; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 25th International Workshop on Languages and Compilers for Parallel Computing, LCPC 2012, held in Tokyo, Japan, in September 2012. The 16 revised full papers, 5 poster papers presented with 1 invited talk were carefully reviewed and selected from 39 submissions.The focus of the papers is on following topics: compiling for parallelism, automatic parallelization, optimization of parallel programs, formal analysis and verification of parallel programs, parallel runtime systems, task-parallel libraries, parallel application frameworks, performance analysis tools, debugging tools for parallel programs, parallel algorithms and applications.
Invited Talk -- Just in Time Load Balancing -- Workshop Papers -- AlphaZ: A System for Design Space Exploration in the Polyhedral Model -- Compiler Optimizations: Machine Learning versus O3 -- The STAPL Parallel Graph Library -- Set and Relation Manipulation for the Sparse Polyhedral Framework -- Parallel Clustered Low-Rank Approximation of Graphs and Its Application to Link Prediction -- OmpSs-OpenCL Programming Model for Heterogeneous Systems -- Compiler Optimizations for Industrial Unstructured Mesh CFD Applications on GPUs -- UCIFF: Unified Cluster Assignment Instruction Scheduling and Fast Frequency Selection for Heterogeneous Clustered VLIW Cores -- A Study on the Impact of Compiler Optimizations on High-Level Synthesis -- FlowPools: A Lock-Free Deterministic Concurrent Dataflow Abstraction -- Task Parallelism and Data Distribution: An Overview of Explicit Parallel Programming Languages -- A Fast Parallel Graph Partitioner for Shared-Memory Inspector/Executor Strategies -- A Software-Based Method-Level Speculation Framework for the Java Platform -- Ant: A Debugging Framework for MPI Parallel Programs -- Compiler Automatic Discovery of OmpSs Task Dependencies -- Beyond Do Loops: Data Transfer Generation with Convex Array Regions -- Workshop Posters -- Finish Accumulators: An Efficient Reduction Construct for Dynamic Task Parallelism -- FlashbackSTM: Improving STM Performance by Remembering the Past -- Kaira: Generating Parallel Libraries and Their Usage with Octave -- Language and Architecture Independent Software Thread-Level Speculation -- Abstractions for Defining Semi-Regular Grids Orthogonally from Stencils.
Keywords: Computer science; Software engineering; Operating systems (Computers).; Computer vision; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Software Engineering; Operating Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics